Design of intention-based assistive robot for upper limb. (3rd June 2017) - Young, Eric M.; Withrow, Thomas J.; Sarkar, Nilanjan
Graphical Abstract: Abstract : Robotic assistive devices for rehabilitation have proven to be beneficial for many individuals with impaired limbs by providing accessible, consistent and cost-effective therapy. However, it is important to acknowledge that many people need an alternative form of assistance for physical impairments, both while undergoing rehabilitation and in the common scenario of rehabilitation providing insufficient improvements. The aim of this paper is to present an intention-detecting assistive robot for upper limb motion, which may serve as a complement to rehabilitation procedures. The proposed system collects real-time data from an eye-tracker and force-sensing resistors to determine the intended movement of the arm of a user and physically assists the said movement. We show that the system is capable of moving an impaired upper limb to a desired position with average errors of less than 5 cm, and in this manner may assist motion required by various activities of daily living for someone suffering from physical impairments in their upper limbs.